Changing mortality patterns in Kimberley Aborigines - Gracey, M.; Sun, W.; Somerford, Peter (Blackwell Publishing, 2015)
Background/Aims: To examine the causes of officially reported deaths from several categories among Aboriginal and non-Aboriginal people in a statistical division of north-west Australia from 2002 to 2011. Methods: A cross-sectional analysis of official Death Registration data to calculate mortality rate ratios (Aboriginal against non-Aboriginal) for that decade in six major International Classification of Disease (ICD)-10 categories. The study setting was the West Kimberley Health District in the far north of Western Australia. Results: Death rates of Aborigines relative to non-Aborigines were much higher, by more than 10 times in some categories. Most of the excess deaths in these categories were due to circulatory diseases, injury and poisonings, neoplasms, diabetes, respiratory, and genitourinary conditions. Conclusion: This study has documented the heavy burden of mortality in West Kimberley Aborigines compared with the pattern found in non-Aboriginal people living in the same region.